FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KABUPATEN BENER MERIAH - Syafutri, Helina (Jurnal Ilmiah Cerebral Medika, 2025)
ABSTRACT Diarrhea disease is still a global problem with high morbidity and mortality in various countries, especially in developing countries. Indonesia is one of the developing countries with a high incidence of diarrheal disease due to high morbidity and mortality. Diarrhea refers to excessive loss of fluids and electrolytes that occurs with the feces not formed. Diarrhea is a condition of defecation frequency more than 3 times a day, as well as liquid stool consistency. Diarrheal disease is caused by many factors including environmental conditions, parental behavior and nutritional fulfillment. This study aims to determine the Factors Related to the Incidence of Diarrhea in Toddlers in the Simpang Tiga Health Center Work Area, Bener Meriah Regency. This type of research is analytical with a cross-sectional design. The population in this study were all mothers who had toddlers in the Simpang Tiga Health Center Work Area, Bukit District, Bener Meriah Regency, totaling 2928 toddlers. The sampling method was carried out using the Slovin formula, obtaining a sample size of 95 samples. The study was conducted from 3 to 10 October 2024 using a questionnaire. The results of this study indicate that to determine the relationship between knowledge and the incidence of diarrhea in toddlers, a P Value of 0.005 (P ≤ 0.05) was obtained, to determine the relationship between information and the incidence of diarrhea in toddlers, a P Value of 0.000 (P ≤ 0.05) was obtained and to determine the relationship between the role of health workers and the incidence of diarrhea in toddlers, a P Value of 0.002 (P ≤ 0.05) was obtained. It is recommended that mothers are willing to prevent diarrhea in their toddlers so that they can reduce morbidity and mortality in toddlers due to diarrhea. Keywords : Incidence of Diarrhea in Toddlers, Knowledge, Information, Role of Health Workers